STRATEGI PEMERINTAH KOTA BUKITTINGGI DALAM PENGELOLAAN SANITASI PERKOTAAN TAHUN 2018 - Fira Rahmatia Ardiani; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Bukittinggi city is one of the cities that started the management of sanitation in 2014 where at this time the condition of urban sanitation can be said to be still minimal. Since the issuance of the Decree of the Mayor of Bukittinggi Number 188.45-131 regarding the Establishment of the Bukittinggi City Sanitation Working Group, the government has begun to manage sanitation. Until then the city of Bukittinggi received a national award in the sanitation category of Nawasis for the first time at the end of 2014. After that the City of Bukittinggi again improved its management of sanitation until finally the City of Bukittinggi again received an award in 2018 in the Best of the Best category.The purpose of this study was to determine (1) the strategy of the city government of Bukittinggi in the management of urban sanitation in 2018 (2) the factors that influence the strategy of the city government of Bukittinggi in the management of urban sanitation in 2018.This study uses qualitative research methods with descriptive type. This method aims to get a true picture of the strategy of the city of Bukittinggi in the management of urban sanitation in 2018.In this study the authors used the strategy proposed by Hadari Nawawi namely Aggressive Strategy, Innovative Strategy and Competitive Strategy as a reference to discuss the strategies used by the Bukittinggi City government in urban sanitation management. Aggressive Strategy in the form of Community-Based Total Sanitation Socialization (STBM), Innovative Strategy in the form of hygiene marching songs, giving rewards in the form of gold through a garbage bank, shopping basket distribution to Dasa Wisma Bukittinggi mothers, distribution of tumblers to adiwiyata elementary school level and SMP along with composting using Biodigester. Furthermore Competitive Strategy in the form of competition carried out by each region and in the end was given an award by Akkopsi. The influencing factors are the high level of commitment between the government and sanitation management carried out in a structured and coordinated manner among the Bukittinggi Sanitation Working Group.Keywords : Government strategy, Urban sanitation management